PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA PERAWAT MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada Perawat Ruangan Instalasi Rawat Inap Kelas I, II, III-A, dan III-B Rumah Sakit Islam Unisma Malang) - Ghofar, Abdul; Azzuhri, Misbahuddin (Jurnal Ilmiah Mahasiswa FEB, 2012)
The purpose of this research is to determine the direct influence of the work environment to the performance of nurses, and the indirect influence of the work environment to the performance of nurses through job satisfaction. This research includes explanatory research. The samples used in this study were 35 nurses Rooms Inpatient Class I, II, III-A, and III-B Islamic Hospital Unisma Malang. The data collected through interviews, documentation, and questionnaires. Data analysis performed using the classical assumption (linearity test, normality test, and heteroskidastity tes). Hypothesis testing with analysis path. The results of this study indicate that (1) there is a direct influence of the work environtmet to job satisfaction, (2) there is a direct influence of the work environment to the performance of nurses, (3) there is a direct influence of job satisfaction to the performance of nurses, (4) there is a indirect influence of the work environment to the performance of nurses through job satisfaction. Keyword : the work environment, job satisfaction, dan the performance of nurses.